Negotiating social change values: the critical role of media literacy in facilitating small and medium enterprises in Malaysia - Raja Suzana Raja Kasim; Zulazli Hashim; Mokhtarrudin Ahmad (2018)
The understanding of the right usage of media literacy within the lens of Small and Medium Enterprises’ needs appear to serve as anchor content for an integrated process of application of skills in facilitating business to grow. In this paper, enterprise utilizes social media to develop effective tools in marketing of their products and make connection to a larger network in business. Despite ample of researches on the influence of media literacy on users; negotiating social change values in the context of small and medium enterprises is scant. Using multiple regression analysis, this paper focuses on SMEs in Malaysia as the wider geographical area and potential growth of businesses make it exciting to gauge the critical role it has on enterprises. Samples derived from the quantitative approach, consists of 165 SMEs with those being in operation of not less than 5 years. The elements of access, analyse, evaluate and create in testing media literacy level had shown a positive and significant relationship with social change values among SMEs. The results indicated that in order to provide SMEs with opportunities to learn the standards-based understanding of the use of media literacy deeply, it is imperative that content be taught in enterprise-centered manner. SMEs need opportunities to grapple with the strategy in media literacy, widely and think for themselves in order to deepen their understanding of its usage that of importance in their business promotion and marketing needs.